RELATIONSHIP OF CHRONIC TONSILLITIS AND CARIES - Abduganiyeva I. G.; Аdurashidova D. N.; Turakhnova F. M.; Khujamberdiyeva D. M. (Web of Journals Publishing, 2024)
Studies have been carried out on the influence of certain diseases of the dent alveolar system on the occurrence of inflammation in the palatine tonsils.
Keywords: Chronic tonsillitis, pain, streptococci, disease, micro flora, dental plaque, caries, research, statistics.